Revision of the genus Adelostoma (Coleoptera: Tenebrionidae). Part 1: subgenus Zarudnionymus Semenov & Bogatchev, 1947 - Purchart, Luboš (Zootaxa, 2012)
The subgenus Zarudnionymus Semenov & Bogatchev, 1947 of the genus Adelostoma Duponchel, 1827 is revised. A. ab-yssinicum obockensis subsp. nov. is described from Djibouti. Adelostoma grandicolle Fairmaire, 1890 syn. nov. from Ka-maran Island (Yemen) is synonymised with A. batesi Haag-Rutenberg, 1872 (Yemen). Lectotypes and paralectotypes aredesignated for A. abyssinicum abyssinicum Haag-Rutenberg, 1872, A. batesi Haag-Rutenberg, 1872 and A. grande Haag-Rutenberg, 1879. Habitus photographs and the key for all known species and subspecies of the subgenus Zarudnionymus are presented, together with distribution map.